Prognostic role of pre-treatment serum ALB in Patients with oropharyngeal cancer: A retrospective cohort study - Zhu, Jiajia; Li, Liang; Duan, Yuansheng; Wu, Yansheng; Wang, Xudong (Frontiers in Oncology, 2022)
Abstract Background: The morbidity of oropharyngeal cancer (OPC) is continuing to rise in numerous developed countries. An accurate prognostic assessment is needed to evaluate the malignant degree or risk classification to optimize treatment. Albumin (ALB) as an independent prognostic indicator of cancer survival has been established in previous studies. This study investigated the prognostic value of pre-treatment serum ALB in OPC patients. Methods: The clinicopathological data of 246 patients diagnosed with OPC from the years 2010 to 2019 were retrospectively analyzed. Analyze the relationship between ALB and clinicopathological characteristics of patients. The optimal cut-off values for ALB were determined via Cutoff Finder (Method for cutoff determination: Survival: significance (log-rank test)). The Cox proportional hazards model was used to perform univariate and multivariate analyses of the serum ALB levels related to overall survival (OS) and disease-free survival (DFS) to determine the independent prognostic factors. Results: The optimal cut-off point for ALB was 39.15 g/L determined via Cutoff Finder. Serum ALB levels were significantly associated with age (P=0.047), Presence of comorbidity (P=0.009), Charlson score index (P=0.007), Hemoglobin (P＜0.001), Neutrophil to Lymphocyte Ratio (P=0.002), Albumin-To-Alkaline Phosphatase Ratio (P＜0.001), Alkaline phosphatase (P=0.005), T stage (P=0.016), and HPV status (P=0.002). In the univariate and multivariate analyses, ALB was found to be an independent prognostic indicator for DFS (HR =0.39, 95% CI:0.23-0.66, P=0.000) and OS (HR =0.46, 95% CI: 0.25-0.83, P=0.01 in OPC patients. Conclusions: Pre-treatment serum ALB could serve as a valuable prognostic biomarker for the prognostic stratification of OPC patients.